When head trauma conceals the cause: status epilepticus due to camphor poisoning - Kulkarni, Raghavendra Gopalrao; G., Prajwal B.; R., Manjunathaswamy; N., Pushpa S. (International Journal of Contemporary Pediatrics, 2025)
A 2-year-old male child presented with status epilepticus following an accidental fall from the bed. Initial management focused on trauma-related seizures, but further evaluation revealed camphor poisoning as the underlying cause which was identified by the presence of a camphor-like odor in the nasogastric aspirate and confirmed by toxicology. This case underscores the importance of thorough clinical assessment and history-taking in cases of unexplained seizures. The patient was successfully treated with supportive care, including intubation, intravenous anticonvulsants, fluid therapy, and discharged in stable condition. Camphor poisoning, a common but under recognized cause of seizures in children, occurs in areas where camphor-containing products are widely available. The best possible outcomes in a child can only be assured when a condition is detected early and managed promptly as supportive management. Additionally, public health measures should be instituted to regulate and restrict access to camphor in order to prevent accidental poisonings.